Chemical Composition and Anti-Urolithiatic Activity of Extracts from Argania spinosa (L.) Skeels Press-Cake and Acacia senegal (L.) Willd - Fatima Ezzahra El oumari; Dalila Bousta; Hamada Imtara; Anissa Lahrichi; Radouane Elhabbani; Ghita El mouhri; Omkulthom Al kamaly; Asmaa Saleh; Mohammad Khalid Parvez; Andriy Grafov; Tarik Sqalli Houssaini (Molecules, 2022)
Ethnobotanical studies have reported the traditional medicinal uses of Acacia senegal (L.) Willd. and Argania spinosa (L.) Skeels against kidney stone formation and other chronic kidney diseases. The present work is undertaken to study the litholytic activity and the inhibiting activity of calcium oxalate crystallization by bioactive compounds identified in Argania spinosa (L.) Skeels press-cake (residue of Argan oil) and in Acacia senegal (L.) Willd. The litholytic activity was studied in vitro on cystine and uric acid stones using a porous bag and an Erlenmeyer glass. The study of the inhibiting activity of calcium oxalate crystallization, was based on temporal measurements of the optical density, registered at a 620 nm wavelength for 30 min using an ultraviolet–visible spectrophotometer. The silylation method was performed to identify phytochemicals, followed by gas chromatography coupled with mass spectrophotometry (GC/MS) analysis. The results show significant litholytic activity of Argania Spinosa press-cake hydro-ethanolic extract on uric acid and cystine stones, respectively, with dissolution rates (DR) of 86.38% and 60.42% versus 3.23% and 9.48% for the hydro-ethanolic extract of Acacia senegal exudate. Furthermore, the percentages of nucleation inhibition are 83.78% and 43.77% (p ˂ 0.05) for Argania spinosa and Acacia senegal, respectively. The results point to the detection of 17 phytochemicals in Argania spinosa press-cake extract, the majority of which are phenolic acids and have potent anti-urolithiatic action.